Board financial expertise and IPO performance: An analysis of U.S. public offerings and withdrawals - Nipper, Marvin (Corporate Ownership and Control, 2021)
Potential investors examine governance characteristics prior to an initial public offering (IPO) to assess the quality and prospects of the issuing firm. One important governance characteristic is board financial expertise, as it provides directors with the relevant knowledge for an IPO process and is valuable for the board’s monitoring duties. Therefore, the purpose of this paper is to examine whether and how board financial expertise affects IPO outcomes. To do so, I employ a sample of 414 completed and 85 withdrawn IPOs that were filed from 2014–2017 at NYSE or NASDAQ. I document that the ratio of directors with financial expertise on the board is negatively associated with the level of underpricing and the probability of IPO withdrawal. The results suggest that particularly outside directors with financial expertise have a positive signaling effect and help to reduce information asymmetry around initial public offerings. Above that, using quantile regression, I find that director financial expertise is most valuable for issuances with high levels of investor uncertainty. Therefore, this study makes important contributions to the corporate governance and IPO literature by providing a comprehensive analysis of the effects of board financial expertise on IPO outcome
Keywords: Initial Public Offerings; Underpricing; Board Composition; Board of Directors; Financial Expertise

Correction to: The Impact of Executives’ Gender, Financial Incentives, and Shareholder Pressure on Corporate Social and Ecological Investments (Schmalenbach Journal of Business Research, (2021), 73, 3-4, (307-338), 10.1007/s41471-021-00122-8) - Theis, Jochen; Nipper, Marvin (Schmalenbachs Zeitschrift für betriebswirtschaftliche Forschung, 2022)
Unfortunately the following typesetting errors appeared after the online publication of the article: On page 17, Fig. 4: the label of the y axis was missing. On page 16, Table 2: error in the top right cell and in the labelling of the first row The original article has been corrected.
CRIS-Team Scopus Importer:2023-11-27

Das Setzen von Emissionsreduktionszielen - Nipper, Marvin (Sustainability Reporting Praxisnahe Informationen und Fallstudien, 2024)
Keywords: Sustainability Reporting; Nachhaltigkeitsberichterstattung; Nachhaltigkeit; SBTi; Nachhaltigkeitsziele

Fallstudie: Decarbonization Pathways - Nipper, Marvin (Sustainability Reporting Praxisnahe Informationen und Fallstudien, 2024)
Keywords: Nachhaltigkeit; Emissionen; Emissionsreduktion; Decarbonization

Internationale Prüfungsforschung: ausgewählte praxisrelevante Forschungsergebnisse des Annual Congress 2021 der European Accounting Association - Nipper, Marvin; Köhler, Annette (Die Wirtschaftsprüfung, 2022)

Mandatory disclosure of standardized sustainability metrics: The case of the EU Taxonomy Regulation - Nipper, Marvin; Theis, Jochen; Ostermaier, Andreas (Corporate Social Responsibility and Environmental Management, 2024)
The European Union's Taxonomy Regulation establishes standardized sustainability metrics and makes disclosure mandatory for many companies, aiming to channel investment into sustainable business. These metrics compete with voluntary third-party sustainability ratings in influencing investors. Using an online vignette study, we examine how green revenue, as an exemplary standardized metric, interacts with a traditional third-party rating to influence investors. We find that green revenue influences investors, but sustainability ratings have an incremental effect, both if green revenue is low and if it is high. Hence, sustainability ratings remain relevant for companies and investors. Our findings contribute to the literature on real effects of reporting regulation and have important implications for mangers and regulator
Keywords: ESG reporting; EU Taxonomy; green revenue; investor decision-making; sustainability reporting

The Impact of Executives’ Gender, Financial Incentives, and Shareholder Pressure on Corporate Social and Ecological Investments - Theis, Jochen; Nipper, Marvin (Schmalenbachs Zeitschrift für betriebswirtschaftliche Forschung, 2021)
Archival research suggests that female executives have an impact on corporate decision-making and generally finds positive associations between female board representation and Corporate Social Responsibility (CSR) performance. However, archival research does not reveal why female executives decide differently in the context of CSR. As this is our starting point, we conduct an experiment and examine executives’ decision-making in terms of CSR investment. While female executives seem to be more oriented towards social and ecological practices, we find strong evidence that participants’ real-world incentive program mainly drives their CSR decision-making. We also examine if selected gender-specific character traits (risk propensity, sustainability attitude, and empathy) cause gender differences in executives’ CSR decision-making. In an exploratory analysis, we furthermore show that executives’ risk propensity affects their CSR decision-making conditional on the level of shareholder pressure they face. Our study contributes to the literature on executives’ decision-making and to the CSR literature by enhancing our understanding of determinants of executives’ CSR decision-making.
CRIS-Team Scopus Importer:2023-11-27
Keywords: Corporate Social Responsibility; CSR; Ecological Investments; Executives’ Decision Making; Gender

The influence of corporate philanthropic donations on private investors' valuation judgments: Experimental evidence - Theis, Jochen; Nipper, Marvin; Meier, Marco (Corporate Social Responsibility and Environmental Management, 2023)
Corporate donations towards disaster relief efforts, often called corporate philanthropic disaster relief (CPDR), are commonplace practice and one critically observed subcategory of CSR, with high visibility in the global media. We investigate whether private investors value firms differently based on their perception of firm's engagement in CPDR. Therefore, we created an experimental investment scenario in which we manipulate the magnitude of a hypothetical Firm Y's CPDR efforts to evaluate investment decisions of private investors recruited from Amazon's Cloud Research platform. Our findings suggest that higher CPDR generally affects private investors' assessment of a firm's value positively. Using a structural equation model and the CSR skepticism concept to examine private investors motive attribution to firms' CPDR, we find that private investors perceive high CPDR as an indicator for honest and values-driven corporate social behavior and a low CPDR as an ingratiating attempt to win favor. Thus, we extend prior research by unveiling through which channels of impact CPDR potentially affects firm value and find an explanation why CPDR can have adverse effects on firm value.
CRIS-Team Scopus Importer:2023-11-27
Keywords: corporate philanthropic disaster response; corporate social responsibility; CSR skepticism; investors' perception; valuation judgment

The role of audit committee chair tenure—A German perspective - Nipper, Marvin (International Journal of Auditing, 2021)
This study empirically examines the association of audit committee chair tenure and various reporting quality measures in a German setting. As the debate about the role of tenure has refuelled since the German corporate governance codex first introduced an upper limit for director tenure in 2019, this topic is of particular importance. My findings show that longer tenured audit committee chairs are positively associated with higher levels of earnings management and negatively associated with the audit report lag and the likelihood of error identification by the German financial reporting enforcement panel. I draw upon social bonding to discuss these findings, which seem to be heterogeneous from a reporting quality perspective. I argue that social bonding between management and the AC chair drives the results for earnings management, while it does not impair the AC chair's influence on the audit process. My findings are important from a regulatory and practical perspective.
CRIS-Team Scopus Importer:2023-11-27
Keywords: audit committee; corporate governance; earnings management; reporting quality

The Use of Process Mining in Assessing the Risk of Material Misstatement during an Audit: Experimental Evidence - Mugwira, Tatenda; Stuart, Iris; Kulset, Ellen; Nipper, Marvin (Journal of International Accounting Research, 2025)
Using auditors from Germany and Norway as participants, we experimentally investigate two issues of importance when auditors use process mining evidence during an audit: determining the stage of the audit when the evidence is relevant and evaluating whether the presentation format of the evidence makes a difference in the relevance of the evidence. In our experiment, auditors make a risk assessment in the planning or the substantive stage of the audit, while receiving evidence from a process mining tool in either a graph or text format. We find that the process mining evidence is more relevant at the substantive stage of an audit than during the planning stage, and that auditors who receive the process mining evidence in graph format find it slightly more relevant than auditors who receive the evidence in text forma